Innovation Space Model: Cross-Sectional Qualitative In-Depth Interviews Describing Customer Perceptions of Strategic Innovation in the Private Transportation Sector of Durban - Magaqa, Olwethu (The IIE, 2018)
Strategic Innovation is essential for the survival and growth of businesses as they operate in volatile environments. Customer needs, economic conditions, technologies, legislative frameworks, competitor actions and industry regulations are constantly changing, thus making it important for businesses to develop dynamic capability. The concept of dynamic capability is closely linked to strategic innovation, and it refers to the ability of a business to “integrate, build and reconfigure internal and external competencies to address rapidly changing environments” (Tecee, 1994 p. 516). South Africa, as a developing country, shows low-levels of innovation and this negatively impacts the economic growth of the country (Joffe, 2017). For many years the private transportation industry reflected this same lack of innovation and remained stagnant (Jenk,2015). In 2013 a radical innovation was introduced to private transportation industry of South Africa and was challenged by traditional incumbents of the industry (Dube, 2015). On the other hand, customers welcomed and fully-utilised the innovation. The repercussions of innovation in this industry have been increased competitive rivalry and violence, as of 2013 these controversial topics have overshadowed the industry. In response to this, the research study needed to be conducted to shift the focus from controversy to an understanding of how innovation in the industry occurred, which elements were innovated, (processes, services delivery, market positioning or the industry paradigm) (Tidd & Bessant, 2014) and how value for customers was created.
Keywords: dynamic capability; Strategic Innovation; private transportation industry; Innovation Space Model; customer perceptions